2001
DOI: 10.1097/00005344-200112000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Nitrendipine and Enalapril Combination Therapy in Mild to Moderate Hypertension: Assessment of Dose-Response Relationship by a Clinical Trial of Factorial Design

Abstract: Hypertension is an important cardiovascular risk factor and the goal of its pharmacologic treatment is to reduce morbidity and mortality. Treatment is usually initiated with a low dose of a single agent and titrated to a higher dose as required. As many as 50% of patients require the addition of a second agent to achieve satisfactory blood pressure control. The aim of this study was to assess the dose-response relationship of nitrendipine and enalapril alone or in fixed combination in the treatment of mild to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…1,110 Combination therapy with 2 drugs from the following list may be considered effective in lowering the patient's blood pressure to target: ␤-blocker/diuretic 104 ; ACE inhibitor/diuretic 111 ; ACE inhibitor/ CCB 102,103,105 ; or ARB/diuretic. 101,106,112 Fixed-dose combination products are listed in Table 9. 110 As an alternative, it is also acceptable to increase the dose of the initial monotherapy agent to achieve a blood pressure target, provided the patient tolerates the increased dose.…”
Section: Blood Pressure-lowering Efficacymentioning
confidence: 99%
“…1,110 Combination therapy with 2 drugs from the following list may be considered effective in lowering the patient's blood pressure to target: ␤-blocker/diuretic 104 ; ACE inhibitor/diuretic 111 ; ACE inhibitor/ CCB 102,103,105 ; or ARB/diuretic. 101,106,112 Fixed-dose combination products are listed in Table 9. 110 As an alternative, it is also acceptable to increase the dose of the initial monotherapy agent to achieve a blood pressure target, provided the patient tolerates the increased dose.…”
Section: Blood Pressure-lowering Efficacymentioning
confidence: 99%
“…71 Based on clinical trial data, the following combinations are considered effective in lowering BP to target levels and potentially in protecting against end-organ damage in African-American patients with hypertension: ACE inhibitor/diuretic, 72 ARB/ diuretic, 51,69,70,73 β blocker/diuretic, 74 and ACE inhibitor/CCB combinations. 64,[75][76][77] Fixed-dose formulations of each of these combinations are approved for use in patients with hypertension and should provide greater convenience to patients. Combination therapy also offers a direct economic benefit to the patient through reduced payment shares toward the cost of the prescription.…”
Section: Benefits Of Combination Therapy In African Americansmentioning
confidence: 99%
“…15 The fixed-dose combination of enalapril 10 mg/ nitrendipine 20 mg has been selected and developed by Grupo Vita for second-line treatment of hypertension according to current regulatory recommendations. 16,17 The dose combination was selected in a factorial study, 18 and then confirmed in two comparative controlled trials against monotherapy with either enalapril or nitrendipine. 19 Another important factor in the use of new antihypertensive agents is their ability to maintain the antihypertensive effect during the complete dose interval.…”
Section: Introductionmentioning
confidence: 99%